Clinical analysis of transurethral holmium laser enucleation in the treatment of benign prostatic hyperplasia with prostatic inflammation: A prospective research study - Zhou, Weijian; Mao, Dongdong; Li, Liang; Liu, Gang; Gao, Guojun; Li, Haikun; Gao, Dianjun (Frontiers in Surgery, 2023)
Objective To investigate the clinical efficacy of holmium laser enucleation of the prostate (HoLEP) in the treatment of benign prostatic hyperplasia (BPH) with prostatic inflammation (PI). Methods We prospectively collected and followed up data on patients with BPH who underwent HoLEP at the Affiliated Hospital of Weifang Medical University between July 2021 and July 2022. According to the postoperative pathological results, the patients were divided into two groups: BPH without PI group (BPH group) and BPH with PI group. Statistical analysis was performed on clinical data, including age and body mass index (BMI), prostate volume (PV), postoperative residual urine volume (PVR), preoperative serum total prostate-specific antigen (tPSA), serum-free prostate-specific antigen (fPSA), preoperative and postoperative maximum urinary flow rate (Qmax), International Prostate Symptom Score (IPSS) before and 3 months after surgery, quality of life index (QoL) before and 3 months after surgery, and postoperative complications. Results A total of 41 patients were included in this study, including 16 in the BPH group and 25 in the BPH with PI group. There were no significant differences in preoperative age, BMI, PV, PVR, tPSA, fPSA, and f/tPSA between the BPH and BPH with PI groups (P > 0.05). The preoperative mean Qmax of the BPH and BPH with PI groups were 9.44 ± 2.449 and 7.52 ± 2.946 [mean ± standard deviation (SD)] ml/s, mean IPSS were 17.75 ± 5.335 and 24.24 ± 5.861 (mean ± SD), and mean QoL were 4.13 ± 0.806 and 4.48 ± 0.8 (mean ± SD), respectively. The postoperative mean Qmax of the BPH and BPH with PI groups were 20.38 ± 4.787 and 14.32 ± 3.827 (mean ± SD) ml/s, mean IPSS were 2.69 ± 1.25 and 5.84 ± 3.579 (mean ± SD), and mean QoL were 0.13 ± 0.342 and 0.92 ± 0.759 (mean ± SD), respectively. In both groups, Qmax significantly increased (P < 0.05) and IPSS and QoL significantly decreased after HoLEP (P < 0.05). Before and after surgery, the Qmax in the BPH with PI group was lower than that in the BPH group, and the IPSS and QoL levels in the BPH with PI group were higher than those in the BPH group (P < 0.05). Compared with the BPH group, the increase in Qmax in the BPH with PI group was smaller and the decrease in IPSS was larger (P < 0.05), but the variation in QoL was not statistically significant (P > 0.05). Conclusion Improvements in Qmax, IPSS, and QoL in BPH patients with PI after HoLEP surgery were lower than those in BPH patients alone. PI may be a predictor of a worse response to surgical treatment. However, more multicenter randomized controlled trials with larger samples and long-term follow-up are needed to verify this.